Students’ Counseling and Teachers’ Moral Integrity Management in Science Education - Victor Tubosun Babalola (Program Studi Pendidikan IPS Unesa, 2022)
This study investigates the concepts of Students’ Counseling and Teachers’ Moral Integrity Management in an Ethno-linguistically Diverse Science Education Schools. It aims to expose another cause of teachers’ moral integrity question and provides suggestions to ensure the hardworking teachers are not discouraged and the schools do not lose public trust. Having adopted a multidisciplinary approach, the study exploited oral interviews and e-library resources as data sources. The dichotomy “Theory X and Y” by Douglas McGregor of 1960 was used as the theoretical frame-work to anchor the study. It was discovered that the use of incomplete statements, ambiguous words and gender sensitive statements during students’ counseling are responsible for misinterpretation of intention which often put teachers’ moral integrity at risk. It was suggested that science teachers should be gender conscious and avoid easily misunderstood statements during students counseling. Also, School Administrators and counseling association of Nigeria should organize workshop for science teachers on the needs to refer low performing students to professional counselors for proper counseling interventions.